CKD-497 inhibits NF-kB signaling and ameliorates inflammation and pulmonary fibrosis in ovalbumin-induced asthma and particulate matter-induced airway inflammatory diseases - Kim, Hyejeong; Choi, Jihye; Seo, Jaeok; Lim, Hyungjoon; Kang, Sung Kwon (Frontiers in Pharmacology, 2024)
Introduction: Air pollution, allergens, and bacterial infections are major contributors to pathological respiratory disorders worldwide. CKD-497, derived from the rhizome of Atractylodes japonica and the fruits of Schisandra chinensis, is known for its ability to relieve cough and facilitate phlegm expectoration. However, its protective action against allergic asthma and fine dust-induced lung inflammation, along with its underlying mechanisms, have not been thoroughly investigated. Methods: In this study, we established mouse models of ovalbumin (OVA)-induced asthma and particulate matter (PM)-induced pulmonary inflammation to evaluate the effects of CKD-497. Mice were administered CKD-497 orally, and various parameters such as airway inflammation, mucus production, and proinflammatory cytokine levels (IL-1β, IL-6, TNF-α) were measured. Additionally, the macrophage cell line RAW264.7 was pretreated with CKD-497 and stimulated with lipopolysaccharide (LPS) to assess inflammation via the NF-kB signaling pathway. Results: Oral administration of CKD-497 effectively attenuated airway inflammation and mucus production in both OVA-induced asthma and PM-induced lung inflammation models. It also significantly decreased the production of proinflammatory cytokines IL-1β, IL-6, and TNF-α. CKD-497 alleviated leukocyte infiltration, including neutrophils, and reduced fibrillary collagen deposition in PM10-treated mice. In vitro, CKD-497 pretreatment inhibited LPS-induced inflammation in RAW264.7 cells through the suppression of the NF-kB signaling pathway. Discussion: CKD-497 shows potent anti-inflammatory effects in mouse models of asthma and PM-induced lung inflammation, potentially mediated by the inhibition of the NF-kB pathway. These findings suggest that CKD-497 could serve as a functional supplement to protect against respiratory diseases by mitigating pulmonary and airway inflammation induced by allergens and air pollution.